2010
DOI: 10.1523/jneurosci.1598-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Apoptosis Induced by Endoplasmic Reticulum Stress Is Regulated by ATF4–CHOP-Mediated Induction of the Bcl-2 Homology 3-Only Member PUMA

Abstract: An increasing body of evidence points to a key role of endoplasmic reticulum (ER) stress in acute and chronic neurodegenerative conditions. Extensive ER stress can trigger neuronal apoptosis, but the signaling pathways that regulate this cell death remain unclear. In the present study, we demonstrate that PUMA, a Bcl-2 homology 3 (BH3)-only member of the Bcl-2 family, is transcriptionally activated in cortical neurons by ER stress and is essential for ER-stress-induced cell death. PUMA is known to be a key tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
228
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(238 citation statements)
references
References 77 publications
5
228
0
Order By: Relevance
“…We found that the expression of FADD, caspase-8 and CHOP was not detected in the ischemic core but were obvious in the peri-infarct area, which may be due to the rapid initiation of necrosis in the ischemic core. Moreover, we observed that the ER stressassociated factors were predominantly expressed in the ischemic penumbra, which is in agreement with previous reports that under severe ER stress, apoptotic pathways can be activated inducing the expression of downstream effectors [36][37][38]. Our findings further revealed that T10 significantly down-regulated the expression levels of FADD, caspase-8, and CHOP in the peri-infarct area.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the expression of FADD, caspase-8 and CHOP was not detected in the ischemic core but were obvious in the peri-infarct area, which may be due to the rapid initiation of necrosis in the ischemic core. Moreover, we observed that the ER stressassociated factors were predominantly expressed in the ischemic penumbra, which is in agreement with previous reports that under severe ER stress, apoptotic pathways can be activated inducing the expression of downstream effectors [36][37][38]. Our findings further revealed that T10 significantly down-regulated the expression levels of FADD, caspase-8, and CHOP in the peri-infarct area.…”
Section: Discussionsupporting
confidence: 92%
“…[19][20][21] CHOP can trigger the downregulation of pro-survival BCL2 and upregulation of pro-apoptotic BH3-only proteins BIM 22,23 or PUMA. 20 Additionally, a recent study proposed that increased protein synthesis driven by ATF4/CHOP after re-initiation of general translation increases the amount of reactive oxygen species, thus leading to apoptosis. 13 Therefore, a slower increase in ATF4 levels could be protective.…”
Section: Discussionmentioning
confidence: 99%
“…Although the expression of the V37E Cx30 mutant did not induce the upregulation of GRP78, which might occur upon the activation of the activating transcription factor 6 (ATF6) pathway (Berridge, 2002), the V37E mutant only moderately induced the expression of ATF4. ATF4 activates cell-deathinitiating caspases, including caspase 3, through the mitochondria-dependent intrinsic cell death pathway (Galehdar et al, 2010;Groenendyk and Michalak, 2005;Malhotra and Kaufman, 2007). By contrast, the ER-stress-induced splicing of XBP1 through activation of IRE1 did not occur in cells that expressed the V37E mutant, suggesting that the mechanism of cell death might be independent of the UPR.…”
Section: The Loss-of-function V37e Mutant Linked To Clouston and Kidmentioning
confidence: 99%